2015
DOI: 10.1111/jpi.12214
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis serotonin N‐acetyltransferase knockout mutant plants exhibit decreased melatonin and salicylic acid levels resulting in susceptibility to an avirulent pathogen

Abstract: Serotonin N-acetyltransferase (SNAT) is the penultimate enzyme in the melatonin biosynthesis pathway in plants. We examined the effects of SNAT gene inactivation in two Arabidopsis T-DNA insertion mutant lines. After inoculation with the avirulent pathogen Pseudomonas syringe pv. tomato DC3000 harboring the elicitor avrRpt2 (Pst-avrRpt2), melatonin levels in the snat knockout mutant lines were 50% less than in wild-type Arabidopsis Col-0 plants. The snat knockout mutant lines exhibited susceptibility to pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
198
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 207 publications
(207 citation statements)
references
References 57 publications
8
198
1
Order By: Relevance
“…Although several physiological roles of melatonin in plants have been characterized [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22], regulation of plant Fe deficiency responses and Fe homeostasis by melatonin have not been reported. The present study provided evidence that exogenous melatonin conferred improved plant adaptation to Fe deficiency by promoting Fe remobilization in Arabidopsis plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several physiological roles of melatonin in plants have been characterized [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22], regulation of plant Fe deficiency responses and Fe homeostasis by melatonin have not been reported. The present study provided evidence that exogenous melatonin conferred improved plant adaptation to Fe deficiency by promoting Fe remobilization in Arabidopsis plants.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a series of adaptive strategies has been evolved to counteract deleterious effects imposed by stressful factors. It has recently been reported that melatonin can increase the resistance of plants to biotic stress via the salicylic acid (SA)- and nitric oxide (NO)-mediated signaling pathways [14,15]. Furthermore, a large number of publications has documented that melatonin positively participates in the alleviation of plant injury by activating endogenous defense systems against various abiotic stresses, such as UV light, cold, heat, drought, and oxidative stress [16,17,18,19,20,21,22], suggesting that melatonin functions as a novel regulator of abiotic stress responses in plants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mitigating effects on abiotic stressors, melatonin participates in the response to pathogen attack as a signaling molecule by enhancing salicylic acid levels, resulting in resistance to infection (Lee et al , 2015. These beneficial effects have been attributed to the induction of an array of genes (Wang et al 2014b;Weeda et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of in vitro and in vivo studies have proven that melatonin targets mitochondria to reduce oxidative stress [29,30,31,32,33,34,35,36]. This results in decreased apoptosis, improved metabolic status, and an elevated survival rate of cultured cells, unicellular organisms, animals, and plants, which suffer with oxidative stress [37,38,39,40,41,42,43,44,45]. The mechanisms of melatonin as a mitochondrial protector not only relate to its excellent free radical scavenging capacity but also to its function as a signaling molecule to upregulate gene expression of antioxidant enzymes [46,47,48] and a spectrum of stress responsive genes [49,50,51,52,53,54,55,56].…”
Section: Introductionmentioning
confidence: 99%